Body composition parameters for predicting the efficacy of neoadjuvant chemotherapy with immunotherapy for gastric cancer - Lin, Guang-Tan; Huang, Jiao-Bao; Lin, Ju-Li; Lin, Jian-Xian; Xie, Jian-Wei; Wang, Jia-Bin; Lu, Jun; Zheng, Chao-Hui; Huang, Chang-Ming; Li, Ping (Frontiers in Immunology, 2022)
Background: Immune checkpoint inhibitors are increasingly used in neoadjuvant therapy for locally advanced gastric cancer. However, the effect of body composition on the efficacy of neoadjuvant therapy has not been reported. Methods: The computed tomography (CT) images and clinicopathological data of 101 patients with locally advanced gastric cancer who received neoadjuvant chemotherapy combined with immunotherapy (NCI) from 2019 to 2021 were collected. The CT image of L3 vertebral body section was selected, and the body composition before and after the neoadjuvant treatment was calculated using the SliceOmatic software, mainly including skeletal muscle index (SMI), subcutaneous adipose index (SAI), and visceral adipose index (VAI). The relationship between body composition and the efficacy and adverse events of NCI was analyzed. Results: Of the 101 patients, 81 with evaluable data were included in the analysis. Of the included patients, 77.8% were male; the median age of all the patients was 62 years, and the median neoadjuvant therapy cycle was three. After the neoadjuvant therapy, 62.9% of the tumors were in remission (residual tumor cells≤50%), and 37.1% of the tumors had no remission (residual tumor cells>50%). Moreover, 61.7% of the patients had treatment-related adverse events (TRAEs), and 18.5% had immune-related adverse events (irAEs). After neoadjuvant therapy, the body mass index (from 23 to 22.6 cm2/m2, p=0.042), SAI (from 34.7 to 32.9 cm2/m2, p=0.01) and VAI (from 32.4 to 26.8 cm2/m2, p=0.005) were significantly lower than those before treatment, while the SMI had no significant change (44.7 vs 42.5 cm2/m2, p=0.278). The multivariate logistics regression analysis revealed that low SMI (odds ratio [OR]: 3.23; 95% confidence interval [CI]: 1.06–9.81, p=0.047), SMI attenuation (△SMI) ≥ 1.8(OR: 1.45; 95%CI: 1.20–3.48, p=0.048), and clinical node positivity (OR: 6.99;95%CI: 2.35–20.82, p=0.001) were independent risk factors for non-remission. Additionally, high SAI is an independent risk factor for irAEs (OR: 14; 95%CI: 1.73–112.7, p=0.013). Conclusion: Low SMI and △SMI≥1.8 are independent risk factors for poor tumor regression in patients with advanced gastric cancer receiving NCI. Patients with a high SAI are more likely to develop irAEs.